Análise e desempenho de um sistema fotovoltaico conectado a uma rede elétrica não-senoidal - Costa, Leonardo Teodosio da (2019)
This work presents an adequate control methodology for a photovoltaic system connected to a three-phase non-sinusoidal electrical network. In this system, the active power injection must be maximum for optimum use of the energy produced by the set of panels. From the construction of the control system with the non-sinusoidal network, an analysis is made in terms of the quality and quantity of the active power and the power factor that is processed by the photovoltaic system. The comparison between the performance of the repetitive control and the resonant control with respect to the presence of harmonics of the network will be presented, verifying their performance when not using Phase Locked Loop. The photovoltaic power generation system connected to the grid is composed of photovoltaic modules, current-fed CC-CC converter Push-Pull, three-legs voltage inverter, inductor-capacitor-inductor filter and simulated in MATLAB® and PSIM® environments.